Meningkatkan Pendidikan Karakter Anak Kesulitan Belajar Melalui Metode Bercerita Pada Mata Pelajaran PPKn di SDN 09 Padang - Fatmawati , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Children learning disabilities have limitations in capturing and understanding the lessons provided by the teacher. Therefore we need a special approach in providing educational materials to children's learning difficulties. One way that felt most suitable in providing character education materials for children learning difficulties is through storytelling. Therefore, the purpose of this research is to find the contribution of character education with storytelling in the field of study Citizenship Education in an effort to improve the soft skills of children's learning difficulties. This type of research is a collaborative action research undertaken to improve and enhance the quality of learning. Through this research is expected child learning difficulties more easily digested material that it gives motivation to learn as well as possible so that the child has a learning difficulty achieving desire in class. The results of this study are: planning of character education in civics education through storytelling in SDN 09 Padang done during the preparation of lesson planning. The preparation of lesson plans in the form of making the syllabus and lesson plan; implementation of character education in civics education through storytelling in SDN 09 Padang using two ways, namely intrakulikuler and extracurricular activities; Evaluation of the implementation of character education in civics education through storytelling in SDN 09 Padang include: the willingness of student learning; ability to cope with the problem of learning; diligence tasks; independent learning; desire to achieve; and learning objectives.